Demonstration of distinct semiconducting transport characteristics of monolayer graphene functionalized via plasma activation of substrate surfaces. (November 2015) - Wang, Po-Hsiang; Shih, Fu-Yu; Chen, Shao-Yu; Hernandez, Alvin B.; Ho, Po-Hsun; Chang, Lo-Yueh; Chen, Chia-Hao; Chiu, Hsiang-Chih; Chen, Chun-Wei; Wang, Wei-Hua
Abstract: We report semiconducting behavior of monolayer graphene enabled through plasma activation of substrate surfaces. The graphene devices are fabricated by mechanical exfoliation onto pre-processed SiO2 /Si substrates. Contrary to pristine graphene, these graphene samples exhibit a transport gap as well as nonlinear transfer characteristics, a large on/off ratio of 600 at cryogenic temperatures, and an insulating-like temperature dependence. Raman spectroscopic characterization shows evidence of sp 3 hybridization of C atoms in the samples of graphene on activated SiO2 /Si substrates. We analyze the hopping transport at low temperatures, and weak localization observed from magnetotransport measurements, suggesting a correlation between carrier localization and the sp 3 -type defects in the functionalized graphene. The present study demonstrates the functionalization of graphene using a novel substrate surface-activation method for future graphene-based applications.